Penguatan Literasi Numerasi untuk Siswa Sekolah Dasar di SDN Merjosari 4 Malang - Nathasa Pramudita Irianti; Antonius Alam Wicaksono; Ahmad Yusuf Kholil; Kardiana Metha Rozhana (Universitas Pahlawan Tuanku Tambusai, 2023)
The ability to read and count is needed by the next generation. Unfortunately, the importance of numeracy literacy to be implemented in schools has yet to be optimized by some schools. One of them is SDN Merjosari 4 Malang. There are not many activities that can be done to increase numeracy literacy in the school. After discussions with the headmaster, it was agreed that several activities would be carried out at school, namely (1) Forum Group Discussion (FGD) with teachers at SDN Merjosari 4 to strengthen Numerical Literacy, and (2) Carry out activities that could optimize Numerical Literacy at SDN Merjosari 4 Malang. The focus of Numeracy Literacy strengthening activities is given to grades 2, 3, and 4. The series of activities planned to be carried out in community service have all been carried out properly. Students feel interested and happy with the activities that have been carried out and hope that activities like this will be carried out in the future.